Towards Reviving the Travel Trade Sector: Assessing the Business Continuity Preparedness of Selected Philippine Travel Companies - Teresita C. Bautista; Arnelyn M. Torres (SUVANNABHUMI, 2025)
Amidst the global pandemic aftermath, the Philippine tourism industry’s revival depends on its supply chain adaptability. This study assesses Business Continuity Plans (BCPs) of selected travel companies in the Philippines. Employing a supply chain business continuity framework, it seeks to uncover prevalent characteristics and status trends within a specific group. Travel companies, vital intermediaries within this chain, play a pivotal role in distributing, aggregating, marketing, and promoting destinations. To navigate uncertainties effectively, these companies must have robust business continuity plans (BCPs) together with adaptive protocols that complement the current situation. Continuous improvements and change management may be evident in its processes and operating procedures. This study assesses selected travel companies’ readiness through a descriptive survey, evaluating their business continuity plans (BCPs). The research aims to uncover the preparedness levels to withstand disruptions and aid the industry’s revival. Findings can inform strategies to enhance resilience, foster growth, and ensure the long-term sustainability of the Philippine tourism industry.